Acute effects of quercetin-3-O-glucoside on endothelial function and blood pressure: a randomized dose-response study - Bondonno, N.; Bondonno, C.; Rich, L.; Mas, E.; Shinde, S.; Ward, Natalie; Hodgson, J.; Croft, K. (American Society for Nutrition, 2016)
Background: Epidemiologic studies have suggested that a flavonoid-rich diet can reduce the risk of developing cardiovascular disease. Certain flavonoids, in particular quercetin, have been shown to ameliorate endothelial dysfunction and reduce blood pressure (BP), possibly by increasing the bioavailability of the potent vasodilator nitric oxide (NO). Several studies have indicated that improvements in measures of cardiovascular health do not occur linearly, but rather, plateau or decrease with an increasing dose of flavonoids. Objectives: We determined whether the acute administration of increasing doses of a common quercetin glycoside (quercetin-3-O-glucoside) improves endothelial function and reduces BP in a dose-dependent manner. We also explored whether any effects were correlated with changes in plasma NO production. Design: A randomized, controlled, crossover study was performed in 15 healthy volunteers who each completed 5 visits with a minimum washout period of 1 wk between testing days. Participants received each of the following 5 interventions in a random order: 1) 0, 2) 50, 3) 100, 4) 200, or 5) 400 mg quercetin-3-O-glucoside. Endothelial function and BP were assessed before and 60 min after intervention. A blood sample was taken before and 90 min after intervention for the analysis of plasma nitrate and nitrite as markers of NO production as well as of plasma quercetin metabolites.Results: Although we observed a significant correlation between the dose of quercetin-3-O-glucoside and plasma concentrations of total quercetin (R2 = 0.52, P < 0.001) and isorhamnetin (R2 = 0.12, P = 0.005), we showed no improvements in endothelial function or BP and no changes in NO production after any dose. Conclusion: From these results, we conclude that there are no acute changes in BP or the NO-mediated endothelium-dependent relaxation of the brachial artery with doses of quercetin ranging from 50 to 400 mg in healthy men and women. This trial was registered at www.anzctr.org.au as ACTRN12615001338550.